Price movers on the stock exchange of Thailand: Evidence from a fully automated order-driven market - Charoenwong, Charlie (Institutional Knowledge at Singapore Management University, 2010)
This study examines trade sizes used by informed traders. The selected sample includes 73 active stocks from the Stock Exchange of Thailand (SET), a pure limit order market, that cover two distinct market conditions of a bull and bear market. Using intraday data, the study finds that large sized trades (i.e., larger than the 75th percentile) account for a disproportionately large impact on changes in traded and quoted prices. This finding compares with the results of studies conducted on U.S. markets that show informed traders employ trade sizes falling between the 40th and 95th percentiles (Barclay and Warner 1993; Chakravarty 2001). Our results support the hypothesis that informed traders on a pure limit order market such as the SET, where there are no market makers, are able to use larger sized trades than those employed by informed traders on U.S. markets.